ANALISIS EFEKTIVITAS PROGRAM MEMBERSHIP CARD DALAM MENCIPTAKAN LOYALITAS AFEKTIF KONSUMEN MATAHARI DEPARTMENT STORE DI SURABAYA - Maatita, Glenn Russell (Kajian Ilmiah Mahasiswa Manajemen, 2013)
The main objective of this study was to identify affective consumer loyalty can be built through the loyalty program. Implementation of loyalty programs are widely applied to companies engaged in retail business such as Matahari Department Store with membership card ownership called the